2014
DOI: 10.1124/dmd.114.056879
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with a Monoclonal Antibody against Methamphetamine and Amphetamine Reduces Maternal and Fetal Rat Brain Concentrations in Late Pregnancy

Abstract: We hypothesized that treatment of pregnant rat dams with a dual reactive monoclonal antibody (mAb4G9) against (+)-methamphetamine [METH; equilibrium dissociation rate constant (K D ) = 16 nM] and (+)-amphetamine (AMP; K D = 102 nM) could confer maternal and fetal protection from brain accumulation of both drugs of abuse. To test this hypothesis, pregnant Sprague-Dawley rats (on gestational day 21) received a 1 mg/kg i.v. METH dose, followed 30 minutes later by vehicle or mAb4G9 treatment. The mAb4G9 dose was 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“… Miller et al (2013) found that, in rats receiving a KLH-conjugated METH-like hapten vaccine (MH6-KLH) and the vaccine succinyl MA (SMA–KLH), higher antibody titer-dependent METH serum concentrations, yet lower METH concentrations, in the CNS were observed, which suggested reduced METH concentrations in the brain. In addition, it was shown that anti-METH/AMP mAb4G9 therapy protected maternal and fetal rat brains from METH-induced damage ( Gentry et al, 2006 ; White et al, 2014 ). Another study reported that a human–mouse monoclonal antibody binding to methylphenidate, named anti-METH antibody (mAB7F9), elicited a significant reduction in the METH concentration ( Ballester et al, 2017 ).…”
Section: Treatment Of Meth-induced Neurotoxicitymentioning
confidence: 99%
“… Miller et al (2013) found that, in rats receiving a KLH-conjugated METH-like hapten vaccine (MH6-KLH) and the vaccine succinyl MA (SMA–KLH), higher antibody titer-dependent METH serum concentrations, yet lower METH concentrations, in the CNS were observed, which suggested reduced METH concentrations in the brain. In addition, it was shown that anti-METH/AMP mAb4G9 therapy protected maternal and fetal rat brains from METH-induced damage ( Gentry et al, 2006 ; White et al, 2014 ). Another study reported that a human–mouse monoclonal antibody binding to methylphenidate, named anti-METH antibody (mAB7F9), elicited a significant reduction in the METH concentration ( Ballester et al, 2017 ).…”
Section: Treatment Of Meth-induced Neurotoxicitymentioning
confidence: 99%
“…While RBT appears to be promising intervention for methamphetamine use, further work is needed, particularly to ascertain whether pejorative attitudes towards methamphetamine might influence reporting rates. Interestingly a recent study showed that treatment with a monoclonal antibody therapy in pregnant rat dams offered maternal and fetal brain protection from adverse drug effects by reducing brain concentrations of methamphetamine [145]. Further work is needed to understand mechanisms underlying risks for methamphetamine use, and individuals for whom interventions might be more effective.…”
Section: Stimulantsmentioning
confidence: 99%
“…Exposure to repeated, high doses of METH (e.g., 10 – 40mg/kg) during pregnancy has been shown to increase dam/pup mortality, significantly reduce birth weight and produce teratogenic effects (Acuff-Smith et al, 1996; White et al, 2014). Notably, repeated administration of more moderate METH doses (e.g., 2.5 – 5mg/kg), before and throughout pregnancy, also has been shown to have profound effects on dams and offspring.…”
Section: Introductionmentioning
confidence: 99%